The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12144-021-02691-7
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of subject-interests development and influence factors in higher education

Abstract: It is a well-studied phenomenon, that throughout the course of studying at university, the motivation for the study program decreases. Correlation between motivation and learners’ behaviour, for example the learning process, achievement or, in the worst case, dropout exist. So there is a need for understanding the development of motivation in detail, like that of subject-interests, and for identifying influence factors, especially for higher education. This panel study examined the development of 4,345 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In terms of trait, there are two well-known types: situational interest is the increased attention toward content and is typically described as a student who is willing to learn with a constructive feeling about it in a particular moment (Fastrich & Murayama, 2020;Schmidt & Rotgans, 2021;Wong et al, 2020), while individual interest is associated to a continuing propensity to reengage with a specific content over time (Hong et al, 2019;Knekta et al, 2020;Quinlan & Renninger, 2022). In addition, this construct is always intellectualized as being content-specific (Kang et al, 2021;Wild, 2022), which proposes that a student may be interested in a particular subject but not in the other way around, or vice versa. Also, interest has been characterized as a complex construct that encompasses two domains: the affective (e.g., positive feeling) and cognitive (e.g., perceived importance) domains (Aslan et al, 2021;Svenningsson et al, 2022).…”
Section: Individual Interest In Philippine Folk Dance and School Enga...mentioning
confidence: 99%
“…In terms of trait, there are two well-known types: situational interest is the increased attention toward content and is typically described as a student who is willing to learn with a constructive feeling about it in a particular moment (Fastrich & Murayama, 2020;Schmidt & Rotgans, 2021;Wong et al, 2020), while individual interest is associated to a continuing propensity to reengage with a specific content over time (Hong et al, 2019;Knekta et al, 2020;Quinlan & Renninger, 2022). In addition, this construct is always intellectualized as being content-specific (Kang et al, 2021;Wild, 2022), which proposes that a student may be interested in a particular subject but not in the other way around, or vice versa. Also, interest has been characterized as a complex construct that encompasses two domains: the affective (e.g., positive feeling) and cognitive (e.g., perceived importance) domains (Aslan et al, 2021;Svenningsson et al, 2022).…”
Section: Individual Interest In Philippine Folk Dance and School Enga...mentioning
confidence: 99%
“…Contrarily, individual interest is a trait that endures over time and is tied to one's consistent inclination toward a certain subject [34,35,36]. Additionally, interest is often interpreted intellectually as being content-specific [37,38]. Thus, there is a wide range in how seriously different students take Physical Education or other subjects.…”
Section: The Nexus Between Individual Interest and School Engagementmentioning
confidence: 99%
“…The failure and abandonment of university studies are issues that concern all countries because of the personal, social, and economic costs they incur. In fact, the recent scientific literature [1][2][3][4][5][6][7] shows a committed and credible interest in fully addressing this need for educational intervention to provide the necessary resources, strategies, and methodologies to the educational scenarios of the 21st century, appealing to the quality of teaching in higher education and targeting the specific educational needs of university students, especially those who are at risk of social exclusion or have objective indicators of socioeconomic vulnerability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, in terms of student motivation, it has been shown that there is a clear relationship between this variable and university dropout cross-culturally, obtaining the same clear positive tie between high motivation and a lower probability of university dropout in different countries and diverse cultural settings [65][66][67][68][69][70][71][72][73]. In fact, a correlation has been found between motivation and positive behavior of students, as well as favorable involvement in the learning process and academic achievement [7,46,[74][75][76][77][78][79][80][81], in such a way that the most motivated students show less disruptive and/or challenging behavior, greater commitment to the learning process, and higher probabilities of achieving academic achievement. In the same way, recent studies have shown that the predictive value of motivation with respect to the probability of dropping out is clear, revealing that students with greater motivation are more resistant to the problem of dropping out, showing greater probabilities of completing the academic year [7,82,83].…”
Section: Key Variablesmentioning
confidence: 99%
See 1 more Smart Citation